Social Workers in Hospice and Palliative Care in Indian Contect: Voices from the field - Pallavi Mech; Dr Vasundharaa S Nair; Dr Priya Treesa Thomas (Journal of Social Work Education and Practice)
Palliative care (PC) is emerging as an important area of practice in healthcare, where social workers’ involvement is vital in supporting patients and families through the many challenges and difficulties inherent in living with a life limiting illness, as well as in identifying opportunities to assist them with the difficult process of end-of-life planning.